MAKNA TEOLOGIS PENGGUNAAN MEDIA â€œIKAT PINGGANG YANG MENJADI LAPUKâ€ DALAM YEREMIA 13:1-11 - Kristiawan, Ragil (Sekolah Tinggi Teologi Kristus Alfa Omega, 2017)
linen shorts is a medium used by God through the prophet Jeremiah to convey His message to Judah. There are two major problems in the use of this medium as conveyed by scholars. The first problem is about the historical value of this story. Some scholars argue that this passage is only the vision experienced by the prophet. But other scholars accept that this passage really happened historically. The problem of meaning from this media also remains a debate. Some scholars accept that this passage is a direct allegory that refers to the Babylonian exile. But other scholars dismiss this rigorous categorization. Finally the researcher concludes that this passage really happened historically in the life of the prophet and has a single meaning that Israel as God's beloved people will eventually be removed from the history of the world as His instrument.